HE DID NOT DESCEND INTO HELL: An Appeal for Scripture Exegesis Karl Barth and Wayne Grudem - Munir, Tjerlang; Susanto, Johanes Lilik (Scriptura Indonesia, 2023)
The theory of the descent into hell, which holds that after his crucifixion, Jesus went into the realm of the dead to free the souls of the righteous who died before his resurrection, has been a source of contention in Christian theology throughout history. Some theologians and researchers have recently questioned the conventional reading of the relevant scripture texts, claiming that the fall into hell is neither required nor true teaching. In this study, we will argue for a careful and responsible interpretation of the key biblical passages to discern the genuine meaning of the fall into hell. I'll start by looking at the doctrine's historical and theological backdrop as well as its evolution in the early church. Then, using 1 Peter 3:19–20, Ephesians 4:8–10, and Acts 2:27–31 as examples, I will examine the scriptural verses that have been used to support or dispute the notion. I'll look at the passages' linguistic, literary, and theological characteristics, as well as their intertextual and cultural context. Based on this exegetical examination, we will argue that the notion of the descent into hell is a theological inference or hypothesis based on a combination of scriptural and non-scriptural sources rather than a necessary or explicit doctrine in the Bible.